Incidence of suicide mortality among childhood cancer survivors: A population-based retrospective study. (October 2021) - Fu, Xue-Lei; Wu, Hua; Qian, Yan; Jin, Xiao-Hong; Yu, Hai-Rong; Du, Lin; Chen, Hong-Lin; Shi, Ya-Qin
Highlights: Incidence of suicide mortality among childhood cancer survivors was 7.1 per 100, 000 person-years. Male survivors and thyroid cancer survivors were associated with higher suicide risk. Suicide remains a problem for childhood cancer survivors. Abstract: The aim of our study was to investigate the suicide rates among childhood cancer survivors and assess factors associated with higher suicide risk. A review of data from Surveillance, Epidemiology, and End Results (SEER) program from 1975 to 2016 was performed for this study. This program is based on the US population and is supported by the US National Cancer Institute (NCI). Survivors diagnosed with childhood cancer were recorded. There were 40 suicides among 567, 233 person-years, giving a suicide rate of 7.1 per 100, 000 person-years. Compared with cancer diagnosed between 10 and 14 years old, survivors with cancer diagnosed between 0 and 4 years old had lower suicide risk. Females had a lower risk of suicide than males. Compared with survivors of thyroid cancer, the aHRs were 0.16 for acute lymphocytic leukemia, 0.15 for nodal Hodgkin's lymphoma, 0.14 for brain cancers and 0.09 for kidney cancers. Most suicides occurred after 15 years old. Suicide was a problem for survivors, especially those with thyroid cancer. Beside treating patients holistically, early psychological interventions such as communicating effectively, providing social support and follow-up care related to psychological health are needed.